A stereoselective synthesis of (+)-boronolide - Ghosh, Arun K. (Tetrahedron Lett, 2000)
A stereoselective synthesis of (+)-boronolide is described. The key steps involve a stereoselective reduction of an α-hydroxy ketone, allylation of an α-hydroxy aldehyde and a ring-closing olefin metathesis of a homoallylic alcohol derived acrylate ester utilizing Grubbs’ catalyst.